Pengaruh Person Job Fit Terhadap Organizational Citizenship Behabior Melalui Work Engagement Pada Karyawan PT. X - Nisa, Dwi Hurun; Rozaq, Khoirur (Universitas Negeri Surabaya, 2024)
This research aims to measure and analyse the influence of person-job fit on organisational citizenship behaviour through work engagement. This research is causal research that uses a quantitative approach. The sampling technique used probability sampling with a saturated type sample, using a total population of 38 people. The data analysis in this research applies SEM-PLS with SmartPLS 3.2.9 software. The results of this research prove that person-job fit has a significant positive effect on organisational citizenship behaviour; person-job fit has a significant positive impact on work engagement. Work engagement has a significant positive effect on organisational citizenship behaviour. Work engagement mediates the relationship between person-job fit and organisational citizenship behaviour. If a company wants to increase organisational citizenship behaviour, the company must be able to provide positive energy as a form of person-job fit to increase employee work engagement.